Metasurface‐based triple‐band high‐gain Fabry–Perot cavity antenna. Issue 12 (28th August 2021) - Joshi, Garima; Ramarao, Vijaya
Abstract: A compact, high gain, single layer substrate‐superstrate configuration based Fabry–Perot cavity (FPC) microstrip patch antenna (MPA) is designed. It consists of a single‐frequency MPA on a substrate, along with a frequency‐selective surface (FSS) which acts as a metasurface‐superstrate. The FSS contains a periodic arrangement of unit cells in a square lattice, where each unit cell is structured by a simple design of H‐shape. It works as a partially reflecting surface and is used as a superstrate by mounting the FSS layer over the conventional patch antenna using a Teflon spacer. Our design of single layer and single resonance FSS structure is used to obtain triple‐band resonance on loading it as a superstrate on the MPA. The enhanced reflection phase of FSS plays a key role in obtaining triple‐band performance. The relationship between the cavity height and the cavity resonance frequency is the foremost reason to achieve triple‐band FPC‐MPA from a single resonance MPA. The prototype antenna is fabricated, and the measured results show that the FPC antenna yields a peak gain of nearly 9.30, 10.00, and 9.60 dB at 8.90, 9.63, and 11.49 GHz, respectively in broad‐side direction in both the planes. Gain enhancement of nearly 6, 4.50, and 5.50 dB, in all the three bands are achieved in both the planes, emphasizing the effect of stacking the superstrate on the conventional patch antenna. The triple‐band frequency response shows 3 dB gain bandwidths of 11.79%, 11.45%, and 9.56% at the three frequencies. A significant improvement in impedance bandwidth has been achieved in the measurements in all the three frequency bands, with the highest bandwidth improvement of 6.71% of the FPC antenna at 11.49 GHz. It is also reconfigurable as its operating frequency can be tuned within the X‐band (8–12 GHz) range by a small change in the spacer thickness. In addition, it shows rotation angle‐independent performance features.